Cellular Modulators of the NRF2/KEAP1 Signaling Pathway in Prostate Cancer - Giovanni Tossetta; Sonia Fantone; Daniela Marzioni; Roberta Mazzucchelli (Frontiers in Bioscience-Landmark, 2023)
Prostate cancer is the second most common malignancy in men worldwide. Prostate cancer can be treated by surgery, radiotherapy and hormone therapy. The latter, in the form of androgen-deprivation therapy is needed to reduce prostate cancer progression at an advanced stage. Several studies demonstrated that oxidative stress is involved in cancer occurrence, development and progression and the Nuclear factor erythroid 2-related factor 2 (NRF2)/Kelch Like ECH Associated Protein 1 (KEAP1) pathway is affected by reactive oxygen species (ROS). Furthermore, the NRF2/KEAP1 signaling pathway has been investigated by several studies related to anti-androgen therapy, biochemical recurrence and radiotherapy. In this review we analysed the current literature regarding the indirect modulators involved in NRF2/KEAP1 pathway regulation and their role as possible therapeutic targets in prostate cancer cells.